2017
DOI: 10.1590/0037-8682-0102-2016
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with syphilis in a Reference Center

Abstract: Introduction:The implementation of the rapid test (RT) for syphilis increases access of vulnerable populations to early diagnosis and treatment, impacting the outcomes of infection. We aimed to assess the prevalence of and factors associated with syphilis in a Center for Testing and Counseling (CTC). Methods: We conducted a cross-sectional study at a Reference Center for sexually transmitted disease (STD) and acquired immune deficiency syndrome in Londrina, Northern Paraná State, Southern Brazil. Data regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 16 publications
(19 reference statements)
4
19
0
7
Order By: Relevance
“…Recent studies conducted in different regions of Brazil showed syphilis prevalence among MSM ranging from 9% to 26.3% emphasizing the need for interventions among this group. [69,13,19,23]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies conducted in different regions of Brazil showed syphilis prevalence among MSM ranging from 9% to 26.3% emphasizing the need for interventions among this group. [69,13,19,23]…”
Section: Discussionmentioning
confidence: 99%
“…[5] Recent studies show that the syphilis epidemic is also largely concentrated among MSM in Brazil. [69] Additionally, syphilis infection is of major concern as its ulcerative lesions facilitate HIV acquisition. The risk of acquiring HIV infection through sexual intercourse is increased 3 to 5 times in individuals who are infected with syphilis compared to those who are not.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Factors, such as condomless anal sex, human immunodeficiency virus (HIV) infection, previous sexually transmitted infections (STIs), and lower education level, have also been associated with increased syphilis. 6 8 …”
mentioning
confidence: 99%
“…A worldwide increase in the number of syphilis cases, including in Brazil, has been reported 14 . In the region covered in this study, we have long been observing such an increase in primary health care settings.…”
mentioning
confidence: 99%